Phylogenetic analysis whithin the pristimantis unistrigatus (anura, craugastoridae) group based on morphological characters (2014)
We present a phylogenetic analysis within the Pristimantis unistrigatus group (Anura, Craugastoridae) of Colombia. Characters from the superficial muscles of the hands and feet as well as external characters were taken for analysis. Most of the muscle characters were observed directly, and some were taken from the literature. Similarly, the external ones were taken mostly from the original descriptions and others from the literature as well. Two matrices were constructed, as the species belonging to this group have changed in recent years with respect to the initially proposed when the group was defined. The results lead us to conclude that the group is not monophyletic, although there are some relationships that are worth to survey because they are kept in the very last cladograms obtained for both proposals. It is suggested that these last relationships should be explored in particular, and the overall group in general, increasing the number of characters and taxa that belong to P. unistrigatus. An open question we left is whether actually is worth to keep these informal taxonomic hierarchy called group within the genera of anurans.